IMPLEMENTASI INSENTIF PAJAK DI KPP PRATAMA PONTIANAK TIMUR - Muhamad Rifqy Arifani; I Gede Komang Chahya Bayu Anta Kusuma (JURNAL PAJAK INDONESIA, 2021)
During the pandemic, There were 37,000 MSMEs that reported very serious impacts, as many as 56 percent of MSMEs decrease in business, 22 percent of MSMEs non performing loan and other problems in distribution and less raw materials. This research aims to determine implementation of tax incentives in borne by goverment at KPP Pratama Pontianak Timur, where the business location of 56% of MSMEs in Pontianak region. This research uses qualitative approaches that focuses on the implementation of of the four factors in communication, resources, disposition and bureaucratic structure and administration contraints. This study involved tax official interviews who helds with the implementation of tax incentive policies. This study involved tax official interviews who helds with the implementation of tax incentive policies. The study reveals that the implementation of tax incentives was submitted 28,23% by taxpayers in 2020. Secondly this research highlights the contraint of taxpayers such as using unfamiliar applications forms, complicated administration and the uncertainty perception of incentives policy. The G Edward III model about success factor for implementing in tax incentive policy was ineffective because of the communication factor and resources. However, other factors such as disposition and bureaucratic structure are good enough and support the implementation of tax incentives